Editor's Choice – Relationship Between Global Limb Anatomic Staging System (GLASS) and Clinical Outcomes Following Revascularisation for Chronic Limb Threatening Ischaemia in the Bypass Versus Angioplasty in Severe Ischaemia of the Leg (BASIL)-1 Trial. (November 2020) - Kodama, Akio; Meecham, Lewis; Popplewell, Matthew; Bate, Gareth; Conte, Michael S.; Bradbury, Andrew W.
Abstract : Objective: The Global Vascular Guideline on chronic limb threatening ischaemia (CLTI) has introduced the Global Limb Anatomic Staging System (GLASS) as a new angiographic scoring system. However, the relationship between GLASS and outcomes following revascularisation has not previously been studied. Methods: Using pre-intervention angiograms the relationship between GLASS and immediate technical failure (ITF), amputation free survival (AFS), limb salvage (LS), overall survival (OS), and freedom from major adverse limb events (FF-MALE) was examined in 377 patients undergoing endovascular therapy (EVT, n  = 213) or bypass surgery (BS, n  = 164) in the Bypass versus Angioplasty in Severe Ischaemia of the Leg (BASIL)-1 trial (randomised 1999–2004). Results: There was no significant difference in GLASS between cohorts. There was a significant relationship between ITF and GLASS in EVT (I 14%, II 15%, III 28%, p  = .049). GLASS was significantly related to AFS (hazard ratio [HR], 1.37; 95% CI 1.01–1.85; p  = .042), LS (HR 1.96; 95 % CI 1.12–3.43; p  = .018), and FF-MALE (HR 1.49; 95% CI 1.04–1.87; p  = .028) in the EVT cohort. In BS patients, there was no relationship between GLASS and these outcomes. FF-MALE was significantly worse after EVT than BS in GLASS II ( p  = .038) and III ( p  = .001). Among the subgroup of patients with femoropopliteal (FP) disease (BS, n  = 109 or EVT, n  = 159), FF-MALE was significantly higher after BS than EVT ( p  < .001). The superiority of BS over EVT with increasing GLASS FP grade was greater in the analysis of patients using vein grafts. Conclusion: In the BASIL-1 cohort, GLASS is associated with outcomes following EVT but not BS. Although further validation in contemporary CLTI cohorts is required, GLASS seems likely be useful in shared decision making and for stratifying patients in future trials.